KORELASI PRODUKSI SUSU DENGAN BCS SAPI FRIESIAN HOLSTEIN LAKTASI PERTAMA DI BBPTU-HPT BATURRADEN - Ningsih, Wida Nur (Jurnal Peternakan Nusantara, 2021)
The purpose of this study was to determine the relationship between milk production of PFH dairy cows with BCS at the first lactation at BBPTU HPT Baturraden. The study was conducted from March 20 to April 20 2018, with research material consisting of 250 production data records and 250 BCS data records that were corrected in lactation months 1 to 10 originating from BBPTU HPT Baturraden. Data analysis shows that milk production has a close relationship with lactation month, the results are shown by the equation y = -0.1223x2 + 0.6068x + 13.493 with R2 of 0.97. These results are reflected in the milk production curve which shows in the first month to the third month that there is an increase in milk production, with peak production being reached in the third month. Average peak milk production is 14.74 liters / head / day and average milk production Daily 12.12 liters / head / day. The results of the BCS analysis show that BCS has a close relationship with the lactation month, the results are shown by the equation y = 2.9133 + 0.0132x2 + 0.0365x shown with R2 of 0.95. The results on the BCS graph show that BCS is increasing as the lactation period progresses, the largest average BCS is obtained 3.79 in the 10th month. The relationship between milk production and BCS based on the analysis shows the equation y = -3,9224x2 + 18,894x - 7,6087, indicated by an R2 of 0.98.